Single-cell RNA-seq reveals the diversity of trophoblast subtypes and patterns of differentiation in the human placenta - Liu, Yawei; Fan, Xiaoying; Wang, Rui; Lu, Xiaoyin; Dang, Yan-Li; Wang, Huiying; Lin, Hai-Yan; Zhu, Cheng; Ge, Hao; Cross, James C.; Wang, Hongmei (Cell research, 2018)
The placenta is crucial for a successful pregnancy and the health of both the fetus and the pregnant woman. However, how the human trophoblast lineage is regulated, including the categorization of the placental cell subtypes is poorly understood. Here we performed single-cell RNA sequencing (RNA-seq) on sorted placental cells from first- and second-trimester human placentas. New subtypes of cells of the known cytotrophoblast cells (CTBs), extravillous trophoblast cells (EVTs), Hofbauer cells, and mesenchymal stromal cells were identified and cell-type-specific gene signatures were defined. Functionally, this study revealed many previously unknown functions of the human placenta. Notably, 102 polypeptide hormone genes were found to be expressed by various subtypes of placental cells, which suggests a complex and significant role of these hormones in regulating fetal growth and adaptations of maternal physiology to pregnancy. These results document human placental trophoblast differentiation at single-cell resolution and thus advance our understanding of human placentation during the early stage of pregnancy.